Phenotypic and genotypic characterization of antibiotic-resistant in Escherichia coli isolates from patients with diarrhea - Mojtaba Bonyadian (Iranian Journal of Microbiology, 2019)
Background and Objectives: Escherichia coli is a common enteric pathogen of human and livevestock. Antibiotic resistance is the main concern of public health. The aim of this study was to detect this bacterium in stool samples of diarrheal patients and identify the phenotypic and genotypic characterizations of antibiotic-resistant isolates such as dfrA1, sul1, citm, tetA, qnr, aac(3)-IV in Shahrekord. Materials and Methods: Two hundred fifty diarrheal stool samples from patients were collected. Microbiological and biochemical examinations were done to detect E. coli. Phenotypic and genotypic antibiotic resistance of the isolates were determined using dick diffusion method and polymerase chain reaction (PCR), respectively. Results: Among 114 E. coli isolates, the least resistance was for gentamicin (0%) and the most resistance was for trimethoprim (79.8%). The resistance to sulfamethoxazole, ciprofloxacin, ampicillin, and tetracycline were 71.05%, 10.5%, 52.63%, and 3.5% respectively. The results of PCR assay revealed that 10 isolates contain sul1, 49 isolates harbor citm, 8 isolates tetA, 36 isolates dfrA1, 11 isolates qnr genes but there was no isolate with aac(3)-IV gene. In comparison between phenotypic and genotypic of the isolates revealed that citm, tetA, dfrA1, qnr, sul1, aac(3)-IV genes covered 42.98%, 7.01%, 31.57%, 9.64%, 8.7%, 0% of the antibiotic resistance, respectively. Conclusion: Our results revealed that all isolates harbor one or more antibiotic resistance genes and that the PCR is a fast practical and appropriate method to determine the presence of antibiotic resistance genes.